Integrating Food and Nutrition Security in a Middle‐Income, Globalized, Food‐Exporting Nation: Thailand's Food Policy Challenge. Issue 2 (1st March 2017) - Kelly, Mathew; Seubsman, Sam‐ang; Dixon, Jane; Banwell, Cathy; Sleigh, Adrian
Abstract : Thailand is deeply linked to the world food system, with food exports key to the country's global connections. It has been a world leader in tackling poverty‐related malnutrition and is food secure at a national level. New challenges are emerging with increases in obesity and diet‐related disease as well as the relative poverty of farmers constraining capacity to avoid non‐sustainable agricultural intensification. Here, we consider Thai enmeshment in the global food trade and impacts on food and nutrition security for farmers and urban consumers. We review past and present policy approaches, and examine the prospects for Thailand to interact with these new challenges.